Aspectual Semantics of the Preterite Form in German (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the aspectual semantics of the preterite tense in the modern German language. The main goal is to analyze various linguistic perspectives on the semantics of the preterite and to identify the reasons for the divergence of opinions among scholars. The study discusses how the preterite form can express both imperfective (processual) and perfective (resultative) meanings, as well as function as an aspectually neutral form.Special attention is given to the relationship between aspectual meaning and verb actional properties, contextual factors, and taxis relations. The analysis is based on the works of E. Koschmieder, Yu. S. Maslov, V. M. Pavlov and B. Kh. Rizaev. The findings indicate that the German preterite represents an aspectually neutral grammatical form combining features of process and completion, making it a multifunctional unit in the German verbal system.